Comparison of PEAK PlasmaBlade™ to conventional diathermy in abdominal-based free-flap breast reconstruction surgery—A single-centre double-blinded randomised controlled trial. Issue 8 (August 2021) - Friebel, T.R.; Narayan, N.; Ramakrishnan, V.; Morgan, M.; Cellek, S.; Griffiths, M.
Summary: Background: Electrosurgery makes dissection with simultaneous haemostasis possible. The produced heat can cause injury to the surrounding tissue. The PEAK PlasmaBlade™(PPB) is a new electrosurgery device which may overcome this by having the ability to operate on a lower temperature, therefore reducing collateral thermal damage. Method: A single-centre, double-blinded, randomised controlled trial (RCT) was conducted which included 108 abdominal-based free-flap breast reconstruction patients who had their flap raise performed using either the PPB ( n  = 56) or the conventional diathermy ( n  = 52). Data were collected during their in-patient stay and out-patient appointments. The primary outcome value was the number of days the abdominal drains were required. Results: Baseline characteristics were similar between the groups, except a significantly lower flap weight in the PPB group. The median number of days the drains were required did not differ significantly ( p  = 0.48; 6.0 days for the diathermy and 5.0 days for the PPB). The total drain output ( p  = 0.68), the inflammatory cytokine in the drain fluid ( p >0.054) and complications ( p >0.24) did not differ significantly between the two groups. At the 2-week follow-up appointment, there was a trend towards less abdominal seromas on abdominal ultrasound ( p  = 0.09) in the PPB group which were significantly smaller ( p  = 0.04). Conclusion: The use of the PPB did not result in a significant reduction of drain requirement, total drain output or inflammatory cytokines but did reduce the size of seroma collections at the 2-week follow-up appointment. Therefore, the use of the PPB device could reduce early seroma formation after drain removal.